2014
DOI: 10.1371/journal.pone.0100286
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Signaling Contributes to the Neuroprotective Effects of Urate against 6-OHDA Toxicity

Abstract: BackgroundMounting evidence shows that urate may become a biomarker of Parkinson's disease (PD) diagnosis and prognosis and a neuroprotectant candidate for PD therapy. However, the cellular and molecular mechanisms underlying its neuroprotective actions remain poorly understood.ResultsIn this study, we showed that urate pretreatment protected dopaminergic cell line (SH-SY5Y and MES23.5) against 6-hydroxydopamine (6-OHDA)- and hydrogen peroxide- induced cell damage. Urate was found to be accumulated into SH-SY5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…Higher levels of serum urate are seen in men compared to women (126) with urate’s reference range in clinical practices being for example, 3.4–7.2 mg/dl for men and 2.4–6.1 mg/dl for women (155), apparently due to renal estrogen effects (156). Its concentration is consistently lower in CSF (30 µmol/l), approximately ten times lower than it peripheral concentration in blood (157, 158). This CSF concentration is dependent on blood urate and integrity of the blood-CSF barrier.…”
Section: Determinants Of Urate Levelsmentioning
confidence: 87%
See 1 more Smart Citation
“…Higher levels of serum urate are seen in men compared to women (126) with urate’s reference range in clinical practices being for example, 3.4–7.2 mg/dl for men and 2.4–6.1 mg/dl for women (155), apparently due to renal estrogen effects (156). Its concentration is consistently lower in CSF (30 µmol/l), approximately ten times lower than it peripheral concentration in blood (157, 158). This CSF concentration is dependent on blood urate and integrity of the blood-CSF barrier.…”
Section: Determinants Of Urate Levelsmentioning
confidence: 87%
“…Urate’s indirect action may actually be more pathophysiologically relevant as studies have shown that without astrocytes present in culture, urate concentrations need to be 100-fold higher (158, 223) or 200 µM and above, whereas CNS concentrations of endogenous urate are typically 10- to 100-fold lower (201, 219). In the presence of astrocytes, lower levels of urate are required (201, 219).…”
Section: Urate In Cellular and Animal Models Of Pdmentioning
confidence: 99%
“…The mechanisms underlying urate's neuroprotective effects are not completely clear, though recent in vitro studies have begun to shed light on urate's targets. These studies showed that urate treatment results in nuclear translocation of the nuclear factor (erythroid-derived 2)-like 2 protein, a master regulator of the response to oxidative stress, and transcriptional activation of its key target genes in primary astrocytic cultures [54,55]. In this model, urate treatment led to a marked increase in glutathione synthesis and release [54].…”
Section: Urate Is Neuroprotective In Several Preclinical Models Of Nementioning
confidence: 99%
“…Another limitation of our findings is that we did not observe a correlation between urate levels and GSH levels measured either in plasma or in the brain (by MRSI), despite a reduction in 3‐NT in plasma. Urate cellular targets are not completely known but may include induction of Nrf2‐mediated antioxidant response pathways that ultimately lead to release of GSH by astrocytes 27, 28. These negative GSH findings may be due to lack of sensitivity of the assays, the lack of a biological effect of inosine on these pathways in humans, or the short duration of exposure to inosine.…”
Section: Discussionmentioning
confidence: 99%
“…High urate levels correlate with improved survival in ALS epidemiologic studies17, 18, 19, 20, 21, 22, 23 and with favorable outcomes in other neurodegenerative diseases, most notably Parkinson's disease (PD) 24, 25, 26. Further, urate is neuroprotective in several models of neurodegeneration 12, 27, 28, 29, 30, 31, 32…”
Section: Introductionmentioning
confidence: 99%